2008
DOI: 10.1002/adma.200801112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Decoupling of Aromatic Molecules from a Metal by an Atomically Thin Organic Spacer

Abstract: Electronic coupling effects of organic adsorbates to metallic surfaces are examined optically. Covering a Au(111) substrate with an ultrathin (∼0.3 nm) nanographene‐like layer of flat lying molecules leads to decoupling of further molecular layers to a large extent. Our work suggests that not only inorganic salts or oxides can be used as insulating spacers but also particular organic monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…2. This means in turn that h-BN serves as a decoupling insulator, a behavior which has been reported before also for a hexa-peri-hexabenzocoronene monolayer on Au(111) and its effect on subsequently grown quaterrylene molecules [50].…”
Section: B Optical In Situ Drs Measurementssupporting
confidence: 70%
“…2. This means in turn that h-BN serves as a decoupling insulator, a behavior which has been reported before also for a hexa-peri-hexabenzocoronene monolayer on Au(111) and its effect on subsequently grown quaterrylene molecules [50].…”
Section: B Optical In Situ Drs Measurementssupporting
confidence: 70%
“…It was found that 1 ML of HBC completely decouples the on-top grown QT electronically from the metal substrate. [199] These monolayer-based A/B systems are expected to be studied further in the future as model systems for both structural relationship as well as the electronic structure at the organic-organic interface.…”
Section: Stacked Monolayers (A/b-type)mentioning
confidence: 99%
“…This situation leads to rather broad and unstructured optical absorption bands usually combined with a strong spectral shift. 34,35,45 Consequently, the resulting spectra bear no resemblance to the monomer spectra (cf. Fig.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%